The Circular Economy in Cities and Regions. Synthesis Report. - (:unkn) unknown (My University, 2020)
Cities and regions play a fundamental role in the transition from a linear to a circular economy, as they are responsible for key policies in local public services such as transport, solid waste, water and energy that affect citizens’ well-being, economic growth and environmental quality. This synthesis report builds on the findings from 51 cities and regions contributing to the OECD Survey on the Circular Economy in Cities and Regions and on lessons learnt from the OECD Policy Dialogues on the circular economy carried out in Groningen (Netherlands), Umeå (Sweden), Valladolid (Spain) and on-going in Glasgow (United Kingdom), Granada (Spain), and Ireland. The report provides a compendium of circular economy good practices, obstacles and opportunities, analysed through the lens of its 3Ps analytical framework (people, policies and places). It concludes with policy recommendations, a Checklist for Action and a Scoreboard to self-assess the existence and level of implementation of enabling governance conditions to foster the transition towards the circular economy in cities and regions.
Keywords: Kreislaufwirtschaft; Stadt; Region; Nachhaltige Entwicklung; Regionale Wirtschaftspolitik; Wirtschaftsweise; Transformation; Governance; Städtevergleich; International